Characteristics of etiological diagnostic workup across the past 10 years in patients with spontaneous intracerebral hemorrhage in a large general hospital. (2nd January 2016) - Wang, Qiuxiao; Lin, Sen; Dong, Wei; Liu, Ming
Abstract: Objective : A swift and accurate diagnosis of etiology would lay the foundation of targeted management for patients with spontaneous intracerebral hemorrhage (SICH). It is unclear what the status of diagnostic workup related to etiology is in Chinese hospitals which treat the majority of the hemorrhagic patients in the world. We aim to demonstrate characteristics on diagnostic workup implemented routinely in both departments of Neurology and Neurosurgery in patients with SICH. Methods : We enrolled patients with SICH from March 2002 to December 2011 from Chengdu stroke registry. Data on diagnostic workup were extracted. Results : A total of 2264 patients diagnosed as SICH with rapid neuroimaging (computed tomography (CT) or magnetic resonance imaging (MRI)) scan were included. Patients in the department of Neurosurgery had a lower median Glasgow Coma Scale (GCS) score and a longer median length of stay. They had a significantly lower proportion of hyperlipidemia and heart disease, but a higher proportion of hypertension, alcohol consumption and history of stroke (all p  < 0.05). Following diagnostic workups were more frequently undertaken in the Neurological Department than in the neurosurgical Department: digital subtraction angiography (DSA), plain CT, plain MRI, carotid duplex ultrasound (all p  < 0.001). However, computed tomography angiography (CTA), contrast-enhanced MRI, and brain biopsy (all p  < 0.001) were implemented more in the Neurosurgical Department. While no difference in the proportion of magnetic resonance angiography (MRA) was found between the two departments, the intracranial vascular imaging (workup contains at least one of CTA, MRA and DSA) was performed more frequently in the Department of Neurosurgery (29.8% vs. 9.1%, p  < 0.001). The independent predictors contribute to the implementation of vascular examinations were gender, age, GCS score on admission, department of patients admitted in and the year patients were hospitalized in (all p  < 0.05). Conclusions : Younger patients, females, with severe stroke onset (evaluated by GCS score), admitted in Department of Neurosurgery and hospitalized in recent years had undertaken more examinations on intracranial vascular. It is an urgency to explore a practical scheme of diagnostic workup for the etiology of SICH.